Synthesis of 1-aroyl-3,5-dimethyl-1H-pyrazoles as Anti-HCV and Anticancer Agents - (:unkn) unknown (BENTHAM SCIENCE PUBL LTD, 2014)
1-Aroyl-3,5-dimethyl-1H-pyrazole derivatives (7-12) were synthesized from some hydrazides (1-6) with acetylacetone (2,4-pentanedione) by microwave irradiation. Their structures were elucidated by FT-IR and 1 H-NMR spectral data and elemental analysis. Compound activities were evaluated against HCV NS5B and in cell based HCV reporters. Compound 8 was the most promising of this series in inhibiting intracellular NS5B activity and HCV RNA replication in reporter cells. The selected compounds 9, 10 and 12 by National Institue of Health were screened for their anticancer activity against 60 human tumor cell lines. Compound 9 (3-[(3,5-dimethyl-1H-pyrazol-1-yl) carbonyl]-2',4'-difluorobiphenyl-4-ol) possessed significant activity against human immortalized myelogenous leukemia (K-562) exhibiting cell growth promotion 30.05%, with inhibition of 69.95% at 10(-5) M concentration. Compounds 3 and 9 were evaluated for cell viability and growth inhibition by K-562 cells of MTT assay, at different doses (10(-6)-10(-2) M). Further, compound 9 exhibited anticancer activity against K-562 cells with IC50 value of 4 mu M. Apoptosis levels of compound 9 were determined for three different concentrations (10(-6), 10(-5) and 10(-3) M) at two time points (24 and 48 h). Compound 9 induced apoptosis of K-562 cells, thus suggesting that compound 9 might be a potential chemopreventive agent for chronic myelogenous leukemia.
Keywords: Anticancer activity; Apoptosis; Diflunisal; Hepatitis C NS5B polymerase; Microwave; Pyrazole; MICROWAVE-ASSISTED SYNTHESIS; NATIONAL-CANCER-INSTITUTE; VIRUS NS5B POLYMERASE; PYRAZOLE DERIVATIVES; BIOLOGICAL EVALUATION; DRUG DISCOVERY; CYTOTOXICITY; INHIBITION; ANTITUMOR